2021
DOI: 10.1090/tran/8337
|View full text |Cite
|
Sign up to set email alerts
|

Traces of powers of matrices over finite fields

Abstract: Let g be a random matrix distributed according to uniform probability measure on the finite general linear group GLn(Fq). We show that Tr(g k ) equidistributes on Fq as n → ∞ as long as log k = o(n 2 ) and that this range is sharp. We also show that nontrivial linear combinations of Tr(g 1 ), . . . , Tr(g k ) equidistribute as long as log k = o(n) and this range is sharp as well. Previously equidistribution of either a single trace or a linear combination of traces was only known for k ≤ cqn, where cq depends … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Theorem 1.4 is about 𝑝 𝑘 (𝑓) when we choose 𝑓 uniformly at random from  𝑛,𝑞 , while Theorems 1.1-1.3 are about 𝑝 𝑘 (𝑓) for a polynomial 𝑓 drawn from the space of possible characteristic polynomials of a matrix from GL 𝑛 (𝔽 𝑞 ) endowed with the uniform measure. As proved in [11,Theorem 1.4], the total variation distance of the law of the first 𝑘 next-to-leading coefficients of det(𝐼 𝑛 𝑇 − g) from the uniform distribution on 𝔽 𝑘 𝑞 tends to 0 as 𝑛 → ∞ for 𝑘 as large as 𝑛 − 𝑜(log 𝑛), so the setup of Theorem 1.4 is not that different from the setup of Theorems 1.1-1.3.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Theorem 1.4 is about 𝑝 𝑘 (𝑓) when we choose 𝑓 uniformly at random from  𝑛,𝑞 , while Theorems 1.1-1.3 are about 𝑝 𝑘 (𝑓) for a polynomial 𝑓 drawn from the space of possible characteristic polynomials of a matrix from GL 𝑛 (𝔽 𝑞 ) endowed with the uniform measure. As proved in [11,Theorem 1.4], the total variation distance of the law of the first 𝑘 next-to-leading coefficients of det(𝐼 𝑛 𝑇 − g) from the uniform distribution on 𝔽 𝑘 𝑞 tends to 0 as 𝑛 → ∞ for 𝑘 as large as 𝑛 − 𝑜(log 𝑛), so the setup of Theorem 1.4 is not that different from the setup of Theorems 1.1-1.3.…”
mentioning
confidence: 94%
“…Let g ∈ GL 𝑛 (𝔽 𝑞 ) be an invertible 𝑛 × 𝑛 matrix over 𝔽 𝑞 chosen according to the uniform probability measure. The first author and Rodgers [11,Theorem 1.1] showed that Tr(g 𝑘 ) equidistributes in 𝔽 𝑞 as 𝑛 → ∞, uniformly for 𝑘 ⩽ 𝑐 𝑞 𝑛 for some sufficiently small 𝑐 𝑞 depending on 𝑞, and the rate of convergence is superexponential. However, nothing beyond 𝑘 = 𝑂(𝑛) was known.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For an overview of random matrix theory over finite fields and in particular cycle index techniques see Fulman [24], and for an overview of rank problems and Stein's method, see Fulman and Goldstein [21]. One of the recent results exploring the similarities between theory over different fields is the work of Gorodetsky and Rodgers [27], on the finite field analogue of the fundamental result of Diaconis and Shahshahani [15] on the convergence of traces of unitary matrices to the normal distribution. Ideas used in [15] rely heavily on representation theory and symmetric function theory.…”
Section: Introductionmentioning
confidence: 99%